Promoting Peace Education through Social Networking - Sharma, Ms. Garima (IJRDO- Journal of Educational Research, 2018)
Education is the means to create individuals with self-reliance, and empower them by awareness to live with respect and dignity in peace and harmony with all. If we wish to create a culture of peace and harmony within human societies which is the need of the hour, peace education becomes very essential. Peace education could be considered as a social process through which peace is achieved. It includes the learning of skills of non-violent conflict resolution and respect for human rights. Peace education needs to be included in the curriculum from the primary stages, and carried forward till the higher ones. Steady advances in ICT propelled education and expansions of new media of communication have enhanced expectations of the common man in almost all spheres of their endeavours, including long-lasting peace. ICT offers immense opportunities to make the teaching and learning of peace more effective. Efficient use of ICT in teaching and learning of peace education will provide ample information which could act as a catalyst for both personal and national development. The thought of peace building through ICT brings to mind the notion of customized messages to meet specific needs or solve particular problems. The current generation is at ease with rapidly changing technology as technology is all-pervasive with smart phones in the pockets of today’s youth. The quintessence of using digital media is to communicate peace. As a precious goal of humanity, peace has to be accomplished and sustained by all plausible ways. Technology and Social Networking can be used effectively, in promoting peace education across the globe, have meaningful communication, and fostering the universal values and behaviours in people on which a culture of peace and non violence is predicted.